2016
DOI: 10.1017/s0007114516000696
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and colorectal cancer: molecular, epidemiological and clinical evidence

Abstract: In many cells throughout the body, vitamin D is converted into its active form calcitriol, and binds to vitamin D receptor (VDR), which functions as a transcription factor to regulate various biological processes including cellular differentiation and immune response. Vitamin D metabolizing enzymes (including CYP24A1 and CYP27B1) and VDR play major roles in exerting and regulating effects of vitamin D. Preclinical and epidemiological studies provide evidence for anticancer effects of vitamin D (in particular, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
115
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(120 citation statements)
references
References 180 publications
(224 reference statements)
4
115
0
1
Order By: Relevance
“…Some reports indicated that calcitriol would enhance radiation sensitivity in colorectal cancer regulated by the epithelial‐mesenchymal transition, for example, in vitro experiment trial of DLD1 and HCT116, 24 hours calcitriol pre‐treatment enhanced the radiation sensitivity by 2.3‐ and 2.6‐fold . Pre‐clinical and epidemiological studies have promoted the anti‐tumour effect of calcitriol, particularly against colorectal cancer which involved in anti‐proliferation, pro‐differentiation, pro‐apoptosis, anti‐angiogenesis, immune modulation and miR regulation . A number of genes are recognized to contain functional vitamin D response elements, which also include OPN .…”
Section: Discussionmentioning
confidence: 99%
“…Some reports indicated that calcitriol would enhance radiation sensitivity in colorectal cancer regulated by the epithelial‐mesenchymal transition, for example, in vitro experiment trial of DLD1 and HCT116, 24 hours calcitriol pre‐treatment enhanced the radiation sensitivity by 2.3‐ and 2.6‐fold . Pre‐clinical and epidemiological studies have promoted the anti‐tumour effect of calcitriol, particularly against colorectal cancer which involved in anti‐proliferation, pro‐differentiation, pro‐apoptosis, anti‐angiogenesis, immune modulation and miR regulation . A number of genes are recognized to contain functional vitamin D response elements, which also include OPN .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple lines of evidence show that vitamin D has protective actions against malignant transformation (9, 1113, 46) and epidemiological studies correlated serum vitamin D with CRC risk (46). However, it is not known how individuals differ in their tissue-specific responses to a fixed dose of 1α,25(OH) 2 D 3 , which, in turn, could impact disease risk irrespective of differences in serum 25(OH)D levels.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome-wide studies have identified thousands of differentially expressed (DE) genes of which many are primary targets of the VDR and show cell type-specificity (7, 8). 1α,25(OH) 2 D 3 is thought to exert its chemoprotective effects in the colon through inhibition of proliferation and induction of differentiation and apoptosis (913), although additional mechanisms are likely and remain understudied. Inactive 25-hydroxyvitamin D (25(OH)D), which is measured in the serum, is converted to 1α,25(OH) 2 D 3 locally in the colonic epithelium (7, 8), and also likely contributes to anti-tumor effects.…”
Section: Introductionmentioning
confidence: 99%
“…It seems like that the effects of both probiotics and vitamin D/VDR in colorectal cancer patients are not conclusive, e.g. as recently reviewed by Dou et al [71] , epidemiological studies have consistently demonstrated a strong inverse association of plasma 25(OH)D concentration with colorectal cancer incidence and mortality. However, the effect of vitamin D intake on colorectal cancer prevention is controversial [7274] .…”
Section: Molecular Mechanisms Of Probiotics In Gi Diseasesmentioning
confidence: 99%